Formulation and characterization of Methyl Eugenol Nanocapsules - Pehere, Pradnya K.; Ahuja, Dharmendra (Journal of Neonatal Surgery, 2025)
Alzheimer's disease (AD) is a neurodegenerative brain disorder that affects memory, thinking, concentration, and judgment, ultimately hindering a person's ability to perform routine daily activities. It is characterized by progressive memory loss, language deficits, depression, agitation, mood disturbances and psychosis. On the other hand, it supports the use of herbal medicines due to their nonspecific antioxidant and anti-inflammatory activity and specific cholinesterase inhibitory activity. The popularity of herbal medicines is also increasing due to their perceived effectiveness, safety and affordability. Methyl Eugenol and terpinol are polyphenolic flavonoid that possesses various neuroprotective effects by attenuating the levels of AChE enzyme, accumulated amyloid β, free radicals and neuroinflammation against Alzheimer's disease (AD). Controlled drug release, increased stability of volatile components, active biodegradable packaging and site-specific drug delivery are important areas of this study. Nanocapsules (NCs) are microscopic spherical shells consisting of a core (liquid or solid) in which the drug is enclosed in a cavity by a characteristic polymer membrane. Different methods are used to obtain Nano capsules, but interphase polymerization methods, Nano deposition for a preformed polymer, polymer coating method are mainly preferred. The most important properties in their preparation are particle size and size distribution, which can be evaluated using various techniques such as FTIR, scanning electron microscopy (SEM), DSC, Zeta potential . Nanocapsules with extremely high reproducibility have a wide range of applications in life sciences. They can be used in genetic engineering, cosmetics, cleaning products, wastewater treatment, application of adhesive components, cancer therapy, neuroprotective activity, nano capsule bandages to fight infection, radiotherapy, and as liposomal nano capsules in food science and agriculture. Improved delivery of bioactive molecules through targeted delivery using nano capsules presents many challenges and opportunities for research and future development of new advanced therapies.